Factors Causing Problematic murabaha Financing and Its Handling at KSPPS BMW Rahmah and KSSU Harum Dhaha Kediri - Fadilah, Adin; Laila Maheswari, Audrey; Tri Puspita Ningrum, Ririn (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2024)
KSPPS Bina Mitra Wahana (BMW) Rahmah Jatim and KSSU Harum Dhaha is a Sharia Cooperative located in the Kediri City area, it has a superior financing product, namely murabaha which is in great demand by members, for additional capital for business purposes. The large amount of financing channeled is inseparable from a risk such as non-performing financing. The existence of problematic financing is certainly caused by several factors. This study aims to determine the factors that cause problematic murabaha financing and its handling. This research uses a qualitative approach, and includes a type of comparative research. The results of this study, which are the factors causing the occurrence of non-performing murabaha financing, the majority of which come from external factors, namely the existence of natural disasters or disasters such as the Covid-1 pandemic, members are unable to manage their business properly, decreased purchasing power, increasingly fierce business competition, using financing funds for other purposes, unstable economic conditions, and government policies that can affect the income of business actors. While the internal factors are the analysis that is less thorough when analyzing the condition of the member's business, the lack of a financing supervision system, and also the lack of human resources. The handling of problematic financing carried out is using Rescheduling, and Restructuring. Adjusted to the condition of the member.